Pemupukan N.P.K.Ca.Mg Berimbang dengan Prinsip Empat Tepat terhadap Kakao Produktip (Theobroma Cacao L.) KLON TSH 858 - Sitohang, Nurdin; Harahap, Erwin M.; Hanum, Chairani; Siregar, Tumpal H.S.; Siregar, Hasril (LPPM Universitas Katolik Santo Thomas Medan, 2025)
Cocoa productivity and its quality are still low (<2 tons ha-1), in order to increase its productivity through fertilization, it is necessary to be tested by using balanced N.P.K.Ca.Mg fertilizer with right formula and dosage. The research was done by 3 field experimental series at the cocoa seed farm (TSH 858 clone) owned by IOPRI at Sei Pancur, Deli Serdang on the altitude of 72 m. The research studies were: (1) the influence of balanced N.P.K.Ca.Mg fertilization; (2) the influence of formula and dosage of N.P.K.Ca.Mg of 12,5 : 10,9 : 16,4 : 10,3 : 4,6 and 12,9 : 11,4 : 16,8 : 10,6 : 4,8; and (3) the influence of the time of applying balanced N.P.K.Ca.Mg fertilization of 12,9 : 11,4 : 16,8 : 10,6 : 4,8 with pruning on cocoa flushing, flowering and pod reserves. The research method included: (1) non-factorial group random design with 6 levels of balanced N.P.K.Ca.Mg fertilization, for research-1; (2) nested factorial group random design with 2 levels (the best) of balanced fertilizer formula and 4 levels of dosage ratio (80%-140%), for research-2; and (3) non-factorial group random design with 4 levels of the time of applying balanced N.P.K.Ca.Mg fertilization related to heavy pruning, for research-3. Research-1 showed that, balanced N.P.K.Ca.Mg 12,5 : 10,9 : 16,4 : 10,3 : 4,6 and 12,9 : 11,4 : 16,8 : 10,6 : 4,8 fertilization indicated the better result on number of flower and pod reserves. Research-2 showed that, the formula of N.P.K.Ca.Mg fertilizer of 12,9 : 11,4 : 16,8 : 10,6 : 4,8 which tended to have the highest ratio of dosage (1,120 g plant-1) indicated the best result on number of flower and pod reserves. Research-3 showed that, application of fertilization 2 weeks after pruning indicated the best result. Potential yields can be increased from 680 kg ha-1 by tentative fertilization to 6,180 kg ha-1 by balanced N.P.K.Ca.Mg 12.9: 11.4: 16.8: 10.6: 4.8 fertilization.